2013
DOI: 10.1186/cc11448
|View full text |Cite
|
Sign up to set email alerts
|

Bench-to-bedside review: Functional hemodynamics during surgery - should it be used for all high-risk cases?

Abstract: The administration of a fluid bolus is done frequently in the perioperative period to increase the cardiac output. Yet fluid loading fails to increase the cardiac output in more than 50% of critically ill and surgical patients. The assessment of fluid responsiveness (the slope of the left ventricular function curve) prior to fluid administration may thus not only help in detecting patients in need of fluids but may also prevent unnecessary and harmful fluid overload. Unfortunately, commonly used hemodynamic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 81 publications
1
31
0
2
Order By: Relevance
“…The ultimate goal of these techniques is to achieve optimal oxygen delivery while avoiding the deleterious complications associated with over- and under-resuscitation. [22, 23] First described decades ago, [22-24] this concept has gained increased attention in the recent years and it has been suggested that it could improve various perioperative outcomes in selected patients. Randomized trials, however, have shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of these techniques is to achieve optimal oxygen delivery while avoiding the deleterious complications associated with over- and under-resuscitation. [22, 23] First described decades ago, [22-24] this concept has gained increased attention in the recent years and it has been suggested that it could improve various perioperative outcomes in selected patients. Randomized trials, however, have shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…48 The dynamic variables arise from heart-lung interactions during positive pressure variation; therefore, any change in tidal volume and /or intrathoracic pressure will affect the interaction. 49 A tidal volume \ 8 mLÁkg -1 decreases this interaction and, thus, decreases the negative predictive value of PPV, SVV, or SPV. In other words, a patient may have a low PPV but may actually be volume responsive.…”
Section: Maintenance Fluid Therapymentioning
confidence: 99%
“…Taken together, these data confirmed that hypotension after beach chair position is frequent and required important fluid and vasopressor administration. This must be interpreted with the knowledge of the critical role of perioperative fluid administration and hemodynamic optimization in postoperative outcome [15,16].…”
Section: Discussionmentioning
confidence: 99%